Comparison of Noninvasive Imaging Modalities for Stenosis Grading in Mesenteric Arteries - Schaefer, P. J.; Pfarr, J.; Trentmann, J.; Wulff, A. M.; Langer, C.; Siggelkow, M.; Groß, J.; Knabe, H.; Schaefer, F. K. W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Objective: To prospectively analyze duplex sonography, CTA, and MRA with respect to stenosis grading of the celiac trunk (TC) and the superior mesenteric artery (SMA), with DSA as the reference.Materials and Methods: 52 subjects were enrolled (mean age: 71). The image quality was graded: 1-insufficient, 2-bad, 3-moderate, 4-good or 5-excellent. Stenosis was graded: 1 (< 25 %), 2 (25 – < 50 %), 3 (50 – 75 %) or 4 (75 %). Two-sided chi-square tests were used to check for correlation of stenosis grading between modalities. The weighted Cohen’s kappa was calculated to assess the strength of correlation. With a threshold of 50 % for non-relevant stenosis vs. relevant stenosis, the sensitivity, specificity, PPV, NPV, and accuracy were calculated.Results: The mean image quality was 3.8 ± 0.7, 3.1 ± 1.0, 4.4 ± 0.7, and 3.8 ± 0.9 for DSA, duplex sonography, CTA, and MRA, respectively. For both TC and SMA, stenosis grading reached a significant level of correlation between each noninvasive modality with DSA (p < 0.001, each). The weighted Cohen’s kappa for duplex sonography/CTA/MRA was 0.94/0.93/0.74, respectively, for the TC and 0.64/0.91/0.56, respectively, for the SMA. Highest sensitivity/specificity/NPV/PPV/accuracy were found for CTA with 100 %/95 %/85 %/100 %/96 % for the TC and with na/98 %/na/100 %/98 %, respectively, for the SMA.Conclusion: CTA provided the best image quality, reached the highest level of agreement and significance in correlation in stenosis grading, and offered the best diagnostic accuracy.
Keywords: arteries; angiography; CT angiography; MR angiography; ultrasound